FRI0167 Patient-Reported Outcomes (PROS) During Treatment with Mavrilimumab, A Fully Human Monoclonal Antibody Targeting GM–CSFR-Alpha, In the Phase IIB Earth Explorer 1 Study. (9th June 2015) - Kremer, J.M.; Burmester, G.R.; Weinblatt, M.; Williams, A.E.; Karlsson, N.; Godwood, A.; Albulescu, M.; Close, D.
Abstract : Background: Active RA significantly impairs patients' health-related quality of life (HRQOL) and physical function. Granulocyte-macrophage colony-stimulating factor (GM–CSF) plays a key role in macrophage activation and RA pathogenesis, including inflammatory and arthritic pain development. A Phase IIa study in active RA demonstrated that mavrilimumab produced clinically meaningful improvements across a variety of PROs. 1 Objectives: To assess mavrilimumab's effects on HRQOL and physical function in RA patients in a 24-week Phase IIb study. Methods: In an RCT (NCT01706926 ), we evaluated the efficacy and safety of 3 subcutaneous mavrilimumab dosages (150 mg, 100 mg, and, 30 mg every other week [eow]) vs. placebo over 24 weeks. Patients with adult-onset RA (18–80 years; DAS28–CRP ≥3.2; ≥4 swollen joints; inadequate response to ≥1 DMARDs) receiving concomitant methotrexate were enrolled. Co-primary endpoints were changes in DAS28–CRP score (Day 1 to Week 12) and ACR20 response (Week 24). PRO endpoints included changes from baseline and percentage responders in patient assessments of pain, HRQOL (SF-36 Mental Component Summary [MCS] and Physical Component Summary [PCS] scores), physical function (HAQ DI), and fatigue (FACIT-F). Patients could enter a long-term, open-label extension study at Week 12 (not reported). Results: 326 patients (mean [SD] age, 51.8 [11.1] years; female, 86.5%) with a mean (SD) DAS28–CRP of 5.8 (0.9) were randomized to mavrilimumab 150, 100, or 30 mg eow, or placebo (N=79, 85, 81, and 81, respectively). Both co-primary endpoints (DAS28–CRP at Week 12; ACR20 at Week 24) were met at all mavrilimumab dosages. At Weeks 12 and 24, all mavrilimumab treatment groups exhibited improvements in pain, SF-36 PCS, SF-36 MCS, HAQ DI and FACIT-F vs. placebo, with >50% of patients receiving mavrilimumab 150 mg eow achieving a clinically meaningful response. At this dosage, significant improvements were demonstrated across all PRO endpoints ( p =0.019 to p <0.001 vs. placebo) at Weeks 12 and 24, except for SF-36 MCS (Week 12; p =0.007, Week 24; p =0.187). Statistically significant improvements in pain were demonstrated for mavrilimumab beginning at Week 1. Of patients receiving mavrilimumab 150, 100, and 30 mg eow with a pain response at Week 12, 66.7% (28/42), 69.2% (27/39), and 72.2% (26/36) maintained responses at Week 24. HAQ DI responses at Week 12 were maintained at Week 24 in 78.8% (41/52), 84.0% (42/50), and 75.0% (33/44) of patients (mavrilimumab 150, 100, and 30 mg eow, respectively). Conclusions: Targeting activated macrophages through inhibition of the GM–CSFR-α pathway with mavrilimumab, especially at a dosage of 150 mg eow, substantially and rapidly reduced RA disease activity. In turn, patients receiving mavrilimumab achieved significant, clinically meaningful, and sustained improvements in PROs that reflected the patients' pain, HRQOL, physical function, and fatigue. The majority of mavrilimumab patients with improvement in pain and physical function at Week 12 sustained these improvements through Week 24 References: Burmester GR, et al. Ann Rheum Dis. 2013;72:1445–52. Acknowledgements: Funded: MedImmune Ltd. Editorial assistance: N Panagiotaki, QXV Communications, UK Disclosure of Interest: J. Kremer Shareholder of: Corrona, Grant/research support from: AbbVie, Amgen, Genentech, Lilly, Pfizer, Consultant for: AbbVie, Amgen, Genentech, Lilly, Pfizer, BMS, Employee of: Corrona, G. Burmester Grant/research support from: AbbVie, Pfizer, UCB, Roche, Consultant for: AbbVie, BMS, Novartis, MedImmune, MSD, Pfizer, UCB, Roche, Speakers bureau: AbbVie, BMS, Novartis, MSD, Pfizer, UCB, Roche, M. Weinblatt Grant/research support from: BMS, UCB, Crescendo Bioscience, Consultant for: MedImmune, AstraZeneca, Amgen, Abbvie, BMS, Crescendo bioscience, Lilly, Pfizer, UCB, Roche, A. Williams Shareholder of: AstraZeneca, Employee of: MedImmune, N. Karlsson Shareholder of: AstraZeneca, Employee of: AstraZeneca, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, M. Albulescu Employee of: MedImmune, D. Close Shareholder of: AstraZeneca, Employee of: MedImmune